Identification of a novel interleukin-6 response element containing an Ets-binding site and a CRE-like site in the junB promoter. - Nakajima, K (1993)
Interleukin-6 (IL-6) activation of the immediate-early gene junB has been shown to require both a tyrosine kinase and an unknown 1-(5-isoquinolinesulfonyl)-2-methylpiperazine (H7)-sensitive pathway. Here we report the identification and characterization of an IL-6 immediate-early response element in the junB promoter (designated JRE-IL6) in HepG2 cells. The JRE-IL6 element, located at -149 to -124, contains two DNA motifs, an Ets-binding site (EBS) (CAGGAAGC) and a CRE-like site (TGACGCGA). Functional studies using variously mutated JRE-IL6 elements showed that both motifs were necessary and sufficient for IL-6 response of the promoter. The EBS of the JRE-IL6 element (JEBS) appears to bind a protein in the Ets family or a related protein which could also form a major complex with the EBSs of the murine sarcoma virus long terminal repeat or human T-cell leukemia virus type 1 long terminal repeat. The CRE-like site appears to weakly bind multiple CREB-ATF family proteins. Despite the similarity in the structure between the JRE-IL6 element and the polyomavirus enhancer PyPEA3, composed of an EBS and an AP1-binding site and known to be activated by a variety of oncogene signals, JRE-IL6 could not be activated by activated Ha-Ras, Raf-1, or 12-O-tetradecanoylphorbol-13-acetate. We show that IL-6 activates JRE-IL6 through an H7-sensitive pathway that does not involve protein kinase C, cyclic AMP-dependent kinase, Ca(2+)- or calmodulin-dependent kinases, Ras, Raf-1, or NF-IL6 (C/EBP beta). The combination of JEBS and the CRE-like site appears to form the basis for the selective and efficient response of JRE-IL6 to IL-6 signals, but not to signals generated by activated Ha-Ras, Raf-1, or protein kinase C.